A critical overview of the current myofascial pain literature – January 2018. Issue 1 (January 2018) - Dommerholt, Jan; Hooks, Todd; Chou, Li-Wei; Finnegan, Michelle
Abstract: The majority of papers included in the quarterly review discuss various aspects of dry needling (DN), which continues to be of interest to researchers and clinicians. A study by Liu et al. is the first paper to examine the effects of DN of acetylcholine, esterase and receptors. The study provides support for the integrated trigger point hypothesis and for DN. A paper by Hightower and colleagues found an intriguing link between low magnesium levels in the drink water supply, vitamin D, and myofascial pain, cancer, tendon ruptures, and colon polyps. Contributions originated in the Brazil, China, Germany, Iran, India, Poland, South Korea, Spain, Taiwan, Turkey, and the US.